The Content and Essence of the Concept of Logical Problem in Primary Education - Karimova Kunduz Ruzibaevna (International Journal on Integrated Education, 2022)
The article discusses problems related to the formation of logical thinking in elementary school students. It provides examples that require logical thinking, the specifics of solving them, their solutions and the logical problems that suitable to them.